2022
DOI: 10.2196/31175
|View full text |Cite
|
Sign up to set email alerts
|

Examining Tweet Content and Engagement of Users With Tweets About Hikikomori in Japanese: Mixed Methods Study of Social Withdrawal

Abstract: Background Hikikomori is a form of severe social withdrawal that is particularly prevalent in Japan. Social media posts offer insight into public perceptions of mental health conditions and may also inform strategies to identify, engage, and support hard-to-reach patient populations such as individuals affected by hikikomori. Objective In this study, we seek to identify the types of content on Twitter related to hikikomori in the Japanese language and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
(59 reference statements)
3
2
1
Order By: Relevance
“…Two previous studies [ 7 , 8 ] have additionally shown that the majority of tweets have reported hikikomori as a problem, which corroborates in the findings of our study, suggesting widespread awareness of the seriousness of the phenomenon.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Two previous studies [ 7 , 8 ] have additionally shown that the majority of tweets have reported hikikomori as a problem, which corroborates in the findings of our study, suggesting widespread awareness of the seriousness of the phenomenon.…”
Section: Discussionsupporting
confidence: 92%
“…The interest of users in a specific topic can be assessed by analysing the number of retweets and likes that each tweet generates [ 48 ]. A study [ 8 ] that explored this phenomenon by analysing tweets had more likes than retweets, similar to our study. This could be attributed to the fact that people are more comfortable to show their interest in the subject, but less inclined to actively share the tweets for wider dissemination.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations